Strain Genotypes of Gibberella fujikuroi mating population A (Fusarium moniliforme) Mapping Population - Jin-Rong Xu; John F. Leslie (Fungal Genetics Reports, 1996)
Genetic maps are useful for researchers outside the originating laboratory only if the strains and markers used in the analysis of the mapping population and the genotypes of the strains composing the mapping population are available for analysis. This brief communication gives the genotypes for the strains that compose a recently constructed mapping population of G. fujikuroi. Strains and probes are available from FGSC.